MOTIVASI INTRINSIK, MOTIVASI EKSTRINSIK, KOMPETENSI DAN KINERJA GURU - Abbas, Yusra (Universitas Ahmad Dahlan, 2013)
AbstrakThese research purposes are: (1) explore the relationship betweenÂ intrinsic motivation with teacherâs performance; (2) explore the relationshipÂ between extrinsic motivation with teacherâs performance; (3) explore theÂ relationship between teacherâs competences withteacherâs performance.Â Data was collected through intrinsic motivarion scale, extrinsic motivationÂ scale, teacherâs competency scale and performance measurement. ThisÂ research is quantitative research with correlational approach. This researchÂ used cluster sampling to select the sample from the population. TheÂ population of this research was 160 junior high school teachers in TernateÂ Utara, while the samples were 105 junior high school teachers. ResearchÂ results show: (1) there was significant correlation between intrinsicÂ motivation with teacherâs performance; (2) there was significant correlationbetween extrinsic motivation with teacherâs performance; (3) there wasÂ significant correlation between teacherâs competences with teacherâsÂ performance.Keywords: competence, extrinsic motivation, intrinsic motivation,Â teacherâs performance